Effectiveness of Reality Therapy Group Training based on Choice Theory on Distress Tolerance and Self-Compassion in Mother with Mentally Disabled Children - Yousefi, Saeed (International Journal of Education and Cognitive Sciences, 2022)
This study aimed to evaluate the effectiveness of group reality therapy training based on choice theory on distress tolerance and self-compassion in mother with mentally disabled children.This study was conducted with a quantitative approach and a semi-expreimental method with a pre-test-post-test design with a control group.The statistical population consisted of al the mothers of mentally disabled children in the city ot Tehran academic year 2021-2022. Using available sampling 30 people were selected as a sample and randomly divided into two group (experimental and control). The participants responded to the distress tolerance qusestionnaires of simon and kahler(2005) and self compassionof tef (2003) in the pre-test and post-test phases. The experimental group received reality theapy training in 7 sessions each week while The control group did not recive intervention during The research period. At the end the research were analyzed with covariance analysis at the significance level of (0/05). The result illustated that the mean scores of distress tolerance and self-compassion in creased significantly in the post-test phase compared to the control group)p